Morphological Alterations in the Peripheral and Central Nervous Systems of Mice Lacking Glial Cell Line-Derived Neurotrophic Factor (GDNF): Immunohistochemical Studies - Granholm, Ann-Charlotte E; Srivastava, Nisha; Mott, Justin L; Henry, Stephanie; Henry, Michael; Westphal, Heiner; Pichel, Jose G; Shen, Liya; Hoffer, Barry J (The Journal of neuroscience, 1997)
Glial cell line-derived neurotrophic factor (GDNF) is a member of the TGF-β superfamily of growth factors with neurotrophic activity on midbrain dopaminergic neurons and on developing and mature motoneurons of the brainstem and spinal cord. To investigate the extent of GDNF dependency of central and peripheral nervous structures during development, we have performed an immunohistochemical analysis of sections from the whole head including brain, peripheral ganglia, developing teeth and tongue, as well as intestines, in mutant mice lacking a part of the third exon that encodes the GDNF protein. As described previously, these null-mutated mice lack most of the enteric nerve plexus and are subject to agenesis or severe dysgenesis of the kidneys. In the present communication, we examined the development of vibrissae and incisor and molar teeth, as well as the innervation of these structures, and found no differences between null-mutated and control mice. A decrease in the immunohistochemical labeling intensity with tyrosine hydroxylase was observed in the superior cervical ganglion (SCG), as well as in the pontine nucleus locus coeruleus, and the sympathetic innervation of blood vessels and glands in the head was significantly decreased. None of the brain nuclei studied exhibited any significant decreases in the total number of neurons, but the packing density of neurons in the nucleus locus coeruleus was decreased. These data indicate that GDNF might be one neurotrophic factor that contributes to the development of central and peripheral noradrenergic neurons.